Implementation of Contractual Agreement Used in Evaluation Study: International Class Program - D matra, sarlita; Ulya, Inayatul; Meliza, Meliza; Nuna, Bhanu Prakash (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This article examines the practical implementation of a contractual agreement within the context of an evaluation study focusing on the International Class Program (ICP). The ICP aims to enhance global learning experiences for students through structured international partnerships. The study explores the effectiveness and challenges of the contractual framework in facilitating program evaluation. Drawing on qualitative and quantitative data from stakeholders involved in the ICP, including administrators, faculty, and students, the analysis highlights key outcomes and areas for improvement. This study explores the significance of contractual agreement in international class program evaluation, emphasizing their role in establishing clear terms and conditions, mitigating risks, and executing research ethics. The study investigates the process of establishing contractual agreement and highlights the importance of understanding their terms. It discusses key aspects such as international class theories, characteristics of contractual agreement in evaluation research, the role of evaluators, and an export evaluation study. The study underscores the vital role of contractual agreement in facilitating research ethics and promoting smooth evaluation process. Findings suggest that while the contractual agreement provides a structured approach to evaluation, its application requires continuous refinement to align with evolving program goals and participant expectations. Recommendations are provided for enhancing the contractual framework to better support comprehensive program assessment and foster sustainable international collaborations in education.